Gamification experience of an educational environment in software engineening: Gamifying a course of agility for software process improvement [Experiencia de gamificación de un entorno educativo en ingeniería de software: Gamificando un curso de agilidad para la mejora de procesos software] (2018)
In the last decade gamification has become as a useful strategy for make work environments more dynamic, specifically because it supports initiatives associated with the increase of performance characteristics of work teams such as motivation and commitment. In addition, in work areas such as education, gamification has spread as a useful strategy for make the classroom more dynamic. On the other hand, in the area of software engineering, the performance and productivity of the work team have been identified as key success factors, with motivation being an essential factor in achieving this success. Therefore, there is an important growth of gamification strategies in the classroom as alternatives to increase the motivation and commitment of the work teams. However, the existing teaching strategies in software engineering omit certain details about how to structure a possible learning environment, such as the classroom. In this work a methodological structure is proposed to gamify an educational environment of software engineering. The objective of this proposal is to contribute to the decrease of causes of failure of software development projects within which is the lack of motivation and commitment as well as social and human factors that affect processes related to software engineering. An example of activities developed in a course of agility for software process improvement of the Universidad de Medellín is presented. The methodological structure proposed was designed using technological tools and web 2.0 tools that managed to accompany the teaching-learning process taking into account defined gamification principles. © 2018 AISTI.